2017
DOI: 10.4103/psychiatry.indianjpsychiatry_190_17
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward psychiatrists and psychiatric medication: A survey from five metropolitan cities in India

Abstract: Background:Stigmatization and overall scarcity of psychiatrists and other mental health-care professionals remain a huge public health challenge in low- and middle-income countries, more specifically in India. Most patients seek help from faith healers, and awareness about psychiatrists and treatment methods is often lacking. Our study aims to explore public attitudes toward psychiatrists and psychiatric medication in five Indian metropolitan cities and to identify factors that could influence these attitudes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Our study adds to the limited literature on the mental health sequalae of reproductive challenges by representing the experiences of vulnerable women who are seldom included. Between the near absolute lack of availability of any type of treatment options and the stigma associated with mental health care [ 18 , 19 ], these women, who include many in need of mental health care, are the least likely to receive it. There is evidence that community mental health awareness programs have made some impact on stigmatization, however, traditional beliefs still deter use of allopathic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study adds to the limited literature on the mental health sequalae of reproductive challenges by representing the experiences of vulnerable women who are seldom included. Between the near absolute lack of availability of any type of treatment options and the stigma associated with mental health care [ 18 , 19 ], these women, who include many in need of mental health care, are the least likely to receive it. There is evidence that community mental health awareness programs have made some impact on stigmatization, however, traditional beliefs still deter use of allopathic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, among the already vulnerable slum dwelling women, the burden of perinatal grief goes unaddressed in the context of the profound mental health treatment gap in the country [ 18 ]. Compounding issues of longstanding stigmatization of mental health and the lack of mental health professionals or programming [ 19 ], provide these women few if any options to seek help. Even women who give birth to a healthy infant are at risk for postnatal depression.…”
Section: Introductionmentioning
confidence: 99%
“…It is approved that there is a gap in the study of resident's beliefs towards the mental health, so there is a need for theoretical and practice frameworks towards the physical and mental health needs, within which, mental health professionals can holistically plan and deliver interventions to improve outcomes. In addition, put team work strategies between different specialties [21].…”
Section: Discussionmentioning
confidence: 99%
“…This could be an embedded cultural belief where in India psychiatry is still not considered an important medical specialty due to societal apprehensions and ignorance 25. This is further substantiated by a recent study among a general population sample in India which found that one third of participants believed that psychiatrists specialise in psychiatry because they are not good enough for other specialties 26. Mental illness stigma needs to be studied within its sociocultural context in order to understand its origins, meanings and consequences27 and in doing so, this may provide great insight into the ethnic differences observed in relation to associative stigma.…”
Section: Discussionmentioning
confidence: 96%